2013
DOI: 10.17816/kmj1924
|View full text |Cite
|
Sign up to set email alerts
|

Lactate concentration in amniotic fluid at early neonatal period in perinatal hypoxia

Abstract: Aim. To determine the prognostic value of lactate concentration in amniotic fluid and umbilical cord blood of newborns at early neonatal period as indicators of increased risk of unfavorable outcome in infants with perinatal hypoxia. Methods. Determination of lactate and creatinine concentration in amniotic fluid at first stage of labor was performed by biochemical means. Determination of lactate concentration in the blood serum of infants at birth and at 3-4 days of life was also performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
0
1
Order By: Relevance
“…The overall median lactate concentration of the amniotic fluid (72 mg/dl) was slightly higher than that reported for humans during normal labour (7.1 ± 1.45 mmol/L, corresponding to 64 ± 13.06 mg/dl) (Korenovsky et al, 2013), but lower in comparison to data (12.5 mmol/l, corresponding to 112.6 mg/dl) reported for late-pregnant cats by Fresno et al (2012). The amniotic fluid lactate con-centrations were also studied in horses (Pirrone et al, 2012), and the mean concentrations reported for foals born from spontaneous eutocic parturition were higher (14.47 mmol/L, corresponding to 130.36 mg/dl) in comparison to data observed in the present study in dogs born by elective Caesarean section.…”
Section: Discussioncontrasting
confidence: 58%
“…The overall median lactate concentration of the amniotic fluid (72 mg/dl) was slightly higher than that reported for humans during normal labour (7.1 ± 1.45 mmol/L, corresponding to 64 ± 13.06 mg/dl) (Korenovsky et al, 2013), but lower in comparison to data (12.5 mmol/l, corresponding to 112.6 mg/dl) reported for late-pregnant cats by Fresno et al (2012). The amniotic fluid lactate con-centrations were also studied in horses (Pirrone et al, 2012), and the mean concentrations reported for foals born from spontaneous eutocic parturition were higher (14.47 mmol/L, corresponding to 130.36 mg/dl) in comparison to data observed in the present study in dogs born by elective Caesarean section.…”
Section: Discussioncontrasting
confidence: 58%